1996
DOI: 10.1017/s003118200006515x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic control of susceptibility toTaenia crassicepscysticercosis

Abstract: We previously reported that genes within the major histocompatibility complex influence the intensity of Taenia crassiceps murine cysticercosis. This genetic control, readily apparent in mice of BALB background, was further studied in H-2 congenic and recombinant B10 mice as well as in BALB/c substrains differing in expression of Qa-2 antigens. Similarly low parasite numbers were found in all B10-derived strains infected, regardless of H-2 haplotype, indicating that the effect of H-2 genes in controlling susce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 32 publications
2
26
0
Order By: Relevance
“…The difference in resistance to Y. pestis that we have observed is likely due to the genetic divergence of the BALB/cJ substrain from the other two BALB/c lines since their separation over 70 years ago (23). In fact, phenotypic differences between BALB/c substrains similar to those observed in this study have been well documented for other diseases including Graves' hyperthyroidism (37), experimental allergic encephalomyelitis (39), and Taenia crassiceps cysticercosis (10).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The difference in resistance to Y. pestis that we have observed is likely due to the genetic divergence of the BALB/cJ substrain from the other two BALB/c lines since their separation over 70 years ago (23). In fact, phenotypic differences between BALB/c substrains similar to those observed in this study have been well documented for other diseases including Graves' hyperthyroidism (37), experimental allergic encephalomyelitis (39), and Taenia crassiceps cysticercosis (10).…”
Section: Discussionsupporting
confidence: 85%
“…Although this region is usually associated with antigen-presenting H-2 genes of adaptive immunity, it also contains many genes associated with innate immune defense, including complement components, certain TNF family members, and stress-related proteins (15). Resistance of mice to a variety of pathogens including Plasmodium berghei (14), T. crassiceps (10), Chlamydia pneumoniae (30), and Streptococcus pyogenes (13) has been mapped to the MHC region. Similar to what we have found for Y. pestis, an early innate immune defense appears to be responsible for the observed resistance to S. pyogenes.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental murine cysticercosis caused by T. crassiceps has been a useful model for understanding and defining the biological factors affecting susceptibility and resistance to this disease. Thus, genetic, immunological, and hormonal factors have been related to resistance in this model (14,15,20,22,31,41). Likewise, some of these observations have been confirmed in the natural hosts for T. solium (30,33,34).…”
mentioning
confidence: 52%
“…Previous studies have demonstrated that the absence of MIF prevents the development of protective immunity against intracellular para- sites such as Leishmania by inhibiting macrophage microbicidal activity rather than by preventing the development of a Th1-like response (38). In experimental cysticercosis, an extraintestinal helminthic infection, several immunological factors have been associated with susceptibility and resistance (14,43). For example, we have previously demonstrated that blocking IFN-␥ results in a higher susceptibility to the parasite (43).…”
Section: Resultsmentioning
confidence: 99%
“…In other human parasitic diseases, it has been demonstrated that gender [10], age [11] and genetic background [12] modulate host susceptibility, although, in most cases, the mechanisms remain to be elucidated. Clear evidence of the relevance of the nonclassic MHC antigen (Q9) and of hormonal factors [13][14][15] has been obtained in experimental murine cysticercosis caused by Taenia crassiceps. Few studies are available on host factors implicated in the susceptibility to T. solium infection.…”
Section: Introductionmentioning
confidence: 99%